Understanding the Reallocation of Displaced Workers to Firms - Paul Brandily; Camille Hémet; Clément Malgouyres (Institute of Labor Economics (IZA), 2022)
We study job displacement in France. In the medium run, losses in firm-specific wage premium account for a substantial share of the overall cost of displacement. However, and despite the positive correlation between premium and productivity in the cross-section of firms, we find that workers are reemployed by high productivity, low labor share firms. The observed reallocation is therefore productivity-enhancing, yet costly for workers. We show that destination firms are less likely to conclude collective wage agreements and have lower participation rates at professional elections. Overall, our results point to a loss in bargaining power.
Keywords: J63; J31; 330; displaced workers; wage; reallocation; productivity; labor share